PENGARUH PENDEKATAN MATEMATIKA REALISTIK TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SD PADA MATERI KELILING DAN LUAS TRAPESIUM DAN LAYANG-LAYANG - Artiani, Yuni; Maulana, M.; Iswara, Prana Dwija (Jurnal Pena Ilmiah, 2017)
This research is based on the problem of Indonesian lag in mathematics that is analyzed based on PISA test result. One of the contributing factors is the problem solving ability of elementary school mathematics that is still low. An alternative way to improve that ability is through learning by realistic mathematics education. The research compares the effectiveness of realistic mathematics education with conventional learning specifically on circumference and area of trapezoidal and kite. The research design uses pretest-posttest control group design. The population of it is all the elementary schools in Ganeas sub-district with sample of SDN Ganeas 1 as experiment class and SDN Wargaluyu as control class that is chosen by random. The research instruments are test of mathematical problem solving ability, observation, note, and interview. The result of research in the level of significance Î± = 0.05 that realistic mathematics education and conventional learning can improve students' mathematical problem solving ability significantly. Students give positive responses to learn with realistic mathematics education. The use of active media and student activities are the supporting factors of learning with realistic mathematics education. Meanwhile, the obstacle factors are that students are not yet accustomed to answerÂ the questions that train the problem solving abilitity of mathematics.